Plastic surgical operative workload in major trauma patients following establishment of the major trauma network in England: A retrospective cohort study. Issue 7 (July 2016) - Hendrickson, S.A.; Khan, M.A.; Verjee, L.S.; Rahman, K.M.A.; Simmons, J.; Hettiaratchy, S.P.
Summary: Introduction: The introduction of major trauma centres (MTCs) in England has led to 63% reduction in trauma mortality. 1 The role of plastic surgeons supporting these centres has not been quantified previously. This study aimed to quantify plastic surgical workload at an urban MTC to determine the contribution of plastic surgeons to major trauma care. Methods: All Trauma Audit and Research Network (TARN)-recorded major trauma patients who presented to an urban MTC in 2013 and underwent an operation were identified retrospectively. Patients who underwent plastic surgery were identified and the type and date of procedure(s) were recorded. The trauma operative workload data of another tertiary surgical specialty and local historical plastics workload data from pre-MTC go-live were collected for comparison. Results: Of the 416 major trauma patients who required surgical intervention, 29% ( n = 122) underwent plastic surgery. Of these patients, 43% had open lower limb fractures, necessitating plastic surgical involvement according to British Orthopaedic Association Standards for Trauma (BOAST) 4 guidance. The overall plastic surgery operative workload increased sevenfold post-MTC go-live. A similar proportion of the same cohort required neurosurgery ( n = 115; p = 0.589). Discussion: This study quantifies plastic surgery involvement in major trauma and demonstrates that plastic surgical operative workload is at least on par with other tertiary surgical specialties. It also reports one centre's experience of a significant change in plastic surgery activity following designation of MTC status. The quantity of plastic surgical operative workload in major trauma must be considered when planning major trauma service design and workforce provision, and for plastic surgical postgraduate training.